SAT0245 Azd9567: a novel oral selective glucocorticoid receptor modulator, demonstrated to have an improved therapeutic ratio compared to prednisolone in pre-clinical studies, is safe and well tolerated in first clinical study. (12th June 2018) - Hendrickx, R.; Hegelund-Myrbäck, T.; Dearman, M.; Prothon, S.; Edenro, G.; Leander, J.; Fuhr, R.; Körnicke, T.; Svanberg, P.; Berggren, A. R.; Drmota, T.; Keen, C.; et al.
Abstract : Background: Glucocorticoids (GC) are highly effective in the treatment of inflammatory diseases but chronic treatment is limited by severe adverse effects including hyperglycemia and bone re-modelling. AZD9567 is a novel, orally delivered, non-steroidal Selective Glucocorticoid Receptor Modulator (SGRM) with the potential to demonstrate an improved therapeutic ratio (TR) compared to steroidal GC such as prednisolone. Objectives: To investigate the effects of AZD9567 and prednisolone on biomarkers of inflammation, glucose metabolism and bone re-modelling in pre-clinical models. To confirm the inhibition of inflammatory biomarker production and to evaluate safety and pharmacokinetics (PK) of AZD9567 in a first clinical study. Methods: The effects on biomarkers of gluconeogenesis (tyrosine aminotransferase, TAT mRNA), bone re-modelling (osteoprotegerin, OPG mRNA) and anti-inflammatory activity (TNFα) were evaluated in vitro using human hepatocytes, an osteoblast cell line and whole blood, respectively. In vivo, effects on plasma insulin and osteocalcin levels were compared with inhibition of whole blood TNFα release in rats. Efficacy was evaluated in an adjuvant-induced rat arthritis model. In a human single ascending dose study the effect of AZD9567 on TNFα inhibition was investigated, together with assessment of safety profile and PK. Results: Potent in vitro anti-inflammatory activity (IC50, u 6.2 nM, 7-fold more potent than prednisolone) was observed, whilst no effect on TAT mRNA expression in human hepatocytes was detected for AZD9567 (prednisolone EC50 92 nM). This resulted in a substantially better TR compared to prednisolone. Furthermore, AZD9567 showed a 7-fold superior TR compared to prednisolone based on OPG mRNA expression in human osteoblasts. An improved profile for AZD9567 was also demonstrated in vivo in the rat (TR of 7.5 for osteocalcin and 3.6 for insulin). Efficacy was demonstrated in the rat arthritis model where an inhibition of joint inflammation was observed (ED50 0.1 mg/kg). In human, AZD9567 was safe and well tolerated after single doses (2–155 mg). The PK properties showed a fast absorption with a median tmax of 0.50 to 1.25 hour and a dose-dependent increase in exposure, with a mean terminal half-life of 3.9 to 6.4 hours, suitable for a once daily dosing regimen. TNFa release was inhibited in a concentration-dependent manner (IC50, u 5.2 nM), consistent with pre-clinical findings. Conclusions: In pre-clinical models, AZD9567 demonstrated anti-inflammatory activity with a reduced effect on gluconeogenesis and biomarkers of bone re-modelling compared to prednisolone. Single oral dosing of AZD9567 was well tolerated and showed good PK properties in healthy subjects. These results support that AZD9567 has the potential to improve the treatment of several inflammatory diseases with a better TR compared to prednisolone. AZD9567 is currently in clinical evaluation in rheumatoid arthritis. Disclosure of Interest: R. Hendrickx Employee of: AstraZeneca, T. Hegelund-Myrbäck Employee of: AstraZeneca, M. Dearman Employee of: AstraZeneca, S. Prothon Employee of: AstraZeneca, G. Edenro Employee of: AstraZeneca (former employee), J. Leander Employee of: AstraZeneca, R. Fuhr Employee of: Parexel International GmbH, T. Körnicke Employee of: Parexel International GmbH, P. Svanberg Employee of: AstraZeneca, A. Berggren Employee of: AstraZeneca, T. Drmota Employee of: AstraZeneca (former employee), C. Keen Employee of: AstraZeneca, U. Eriksson Employee of: AstraZeneca